Equivalent energy release rate and crack stability in the End Notched Flexure with inserted roller mixed mode I/II test. (February 2017) - Boyano, A.; De Gracia, J.; Arrese, A.; Mujika, F.
Highlights: Crack propagation performance analysis of the End Notched Flexure with inserted roller test configuration. New equivalent energy release rate definition to analyze mixed mode I/II fracture. Assessment of crack propagation stability under displacement control. Abstract: The crack propagation performance of the End Notched Flexure with inserted roller test is analyzed. An equivalent energy release rate is proposed taking into account the interaction of the modes I and II, based on the linear failure criterion. Experimental results obtained with specimens of F593/T300 carbon/epoxy unidirectional composite show a good agreement with the proposed approach. The stability condition is theoretically developed based on the derivative of the equivalent energy release rate, under fixed load condition and fixed displacement condition. Experimental tests have been carried out to assess the proposed equivalent energy release rate and to evaluate the crack stability condition. An analysis of the influence of compliance measurement on the crack length and on the equivalent energy release rate is included. Based on the results obtained, test conditions with initial mode ratios between 65% and 75% are recommended.